2021
DOI: 10.3390/cancers13164068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Childhood Acute Lymphoblastic Leukemia: Interactions with Clinical Features and Treatment Response

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer among children. This aggressive cancer comprises multiple molecular subtypes, each harboring a distinct constellation of somatic, and to a lesser extent, inherited genetic alterations. With recent advances in genomic analyses such as next-generation sequencing techniques, we can now clearly identify >20 different genetic subtypes in ALL. Clinically, identifying these genetic subtypes will better refine risk stratification and determine the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 157 publications
(275 reference statements)
0
15
0
Order By: Relevance
“…Previous studies showed that the ETV6 :: RUNX1 -like subtype had a relatively favorable outcome with very few reported relapses [ 130 , 179 ]. However, recent studies proved that it had poorer outcomes compared to ETV6 :: RUNX1 [ 180 ]. Additionally, among the 16 B-ALL subtypes, ETV6 :: RUNX1 -like patients had the worst five-year EFS rates along with KMT2A -rearranged and MEF2D-rearranged ALL patients.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the ETV6 :: RUNX1 -like subtype had a relatively favorable outcome with very few reported relapses [ 130 , 179 ]. However, recent studies proved that it had poorer outcomes compared to ETV6 :: RUNX1 [ 180 ]. Additionally, among the 16 B-ALL subtypes, ETV6 :: RUNX1 -like patients had the worst five-year EFS rates along with KMT2A -rearranged and MEF2D-rearranged ALL patients.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…However due to the small number of patients with ETV6 :: RUNX1 -like ALL (9), more studies are required in this field [ 181 ]. It is possible that an ETV6 :: RUNX1 -like subtype may benefit from higher-intensity therapy [ 180 ].…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Different study groups, such as the UKALL, NOPHO, AALL0031 and COG studies, consistently stratify near-haploid and low-hypodiploid B-ALL subtypes as high-risk based on the poor prognosis of the patients, which does not depend on treatment era or on the NCI risk group in which they are classified [ 24 , 26 , 71 ]. In view of the poor prognosis of patients with hypodiploid B-ALL, they have been classically treated with high-dose chemotherapy followed by allogeneic transplantation.…”
Section: Outcome and Treatment Strategies For B-all With Hypodiploidies <40 Chromosomesmentioning
confidence: 99%
“…ALL is a genetically heterogeneous disease [13,34]. The National Cancer Institute (NCI) standard-risk (SR) criteria, presenting age of 1 to 10 years and WBC count < 50 × 10 9 /L), are simple yet surprisingly effective risk stratification criteria [35].…”
Section: The Importance Of the Nci Standard-risk (Sr) Criteriamentioning
confidence: 99%
“…The National Cancer Institute (NCI) standard-risk (SR) criteria, presenting age of 1 to 10 years and WBC count < 50 × 10 9 /L), are simple yet surprisingly effective risk stratification criteria [35]. Favorable genetic drivers, such as hyperdiploidy and ETV6-RUNX1, form the largest proportion of NCI SR patients [34]. In MS2003 [18], age remained prognostically significant for event-free survival (Figure 1).…”
Section: The Importance Of the Nci Standard-risk (Sr) Criteriamentioning
confidence: 99%